Alice in Borderland. Volume 3 - Aso, Haro, 1980- (Viz signature., 2022)
"Eighteen-year-old Ryohei Arisu is sick of his life. School sucks, his love life is a joke, and his future weighs on him like impending doom. As he struggles to exist in a world that can't be bothered with him, Ryohei feels like everything would be better if he were anywhere else. When a strange fireworks show transports him and his friends to a parallel world, Ryohei thinks all his wishes have come true. But this new world isn't an empty paradise, it's a vicious game. And the only way to survive is to play. Aguni now has control of the Beach, and one of his first actions as king is to lock Ryohei in a room on one of the empty floors of the hotel to die of an expired visa. But Ryohei gets an unexpected stay of execution when the Beach becomes the arena for a brutal game of Hearts! Can he survive a witch hunt and get his visa extended, or has he just traded one terrible death for another?"--Back cover.